Aplikasi Sistem Informasi Lelang Ikan Cupang Berbasis Web Pada Fish Betta Ciputat - Setiyawan, Candra; Santoso, Bambang (Scientia Sacra: Jurnal Sains, Teknologi dan Masyarakat, 2022)
There are not many cup fish sales and auctions to implement the online store website. Fish Betta Ciputat has been one of the listings of hickey fish that haven't implemented online store websites. The sales and auctions made by Fish Betta Ciputat only use social instagram, which causes some problems, such as not being able to sort out Numbers and not being able to see the identity of auctioneers like phone Numbers, so it is difficult to follow up on the transaction process.The applications for a hickey fish auction on web-based Fish Betta Ciputat are built to address the problem. Using this application the transaction process can become more structured. The system development method used is the waterfall model..Research has a website that can be used to do transaction proceedings on Fish Betta Ciputat.